Demographic, socioeconomic, and biological correlates of hypertension in an adult population: evidence from the Bangladesh demographic and health survey 2017-18 - Afrin Iqbal; Karar Zunaid Ahsan; Kanta Jamil; M. Moinuddin Haider; Shusmita Hossain Khan; Nitai Chakraborty; Peter Kim Streatfield (BMC, 2021)
Abstract Background Bangladesh is well advanced in the epidemiologic transition from communicable to noncommunicable diseases, which now account for two out of three deaths annually. This paper examines the latest nationally representative hypertension prevalence estimates, awareness, treatment, and control-to identify their association with potential correlates. Methods The analyses are based on the recent Bangladesh Demographic and Health Survey 2017-18 data. Univariate analyses and bivariate analyses between the outcome variables and individual covariates were carried out. Then chi-square tests were done to see the proportional differences between them. To examine the demographic, socioeconomic and biological factors affecting hypertension, awareness, treatment and control, we used multivariate logistic regression models. Results We found that prevalence of hypertension for females and males together aged 35 or more has risen by half between 2011 (25.7%) to 2017 (39.4%). With the broader age range used in 2017, the prevalence is now 27.5% in the population aged 18 years or more. The factors associated with hypertension included older age, being female, urban residence, higher wealth status, minimal education, higher body mass index and high blood glucose level. Following multivariate analyses, many of these characteristics were no longer significant, leaving only age, being female, nutritional status and elevated blood glucose level as important determinants. Over half (58%) of females and males who were found to be hypertensive were not aware they had the condition. Only one in eight (13%) had the condition under control. Conclusion In the coming years, a rising trend in hypertension in Bangladeshi adults is expected due to demographic transition towards older age groups and increase in overweight and obesity among the population of Bangladesh. With more women being hypertensive than men, a targeted approach catering to high risk groups should be thoroughly implemented following the Multisectoral NCD Action Plan 2018-2025. Acting in close collaboration with other ministries/relevant sectors to bring an enabling environment for the citizens to adopt healthy lifestyle choices is a prerequisite for adequate prevention. While screening the adult population is essential, the public sector cannot possibly manage the ever-expanding numbers of hypertensives. The private sector and NGOs need to be drawn into the program to assist.